Antioxidant activities of cocoa bean shell from North Luwu and Gunungkidul as an active compound of packaging material. Issue 1 (May 2021) - Utami, R R; Jamilah; Wahyudi, R; Tangkin, W P; Thamrin, I; Amalia, A N; Indriana, D; Rosniati; Yumas, M; Assa, A; Ariyanti, M
Abstract: The development of the cocoa processing industry must balance with the handling of cocoa bean shell waste. Cocoa bean shell is by product from cocoa processing industry. Active compounds of cocoa bean shell show antioxidant activity as antimicrobial. Based on this information, the cocoa bean shell has the potential to be used as an active compound in the packaging. The objective of this study was to evaluate the antioxidant activity of cocoa bean shell extract from North Luwu and Gunungkidul. Both regions had differences in cocoa bean processing and it may affect the antioxidant activity. The extraction of an active compounds was carried out by preparation of cocoa bean shell powder, defatted with hexane, then extracting active compounds with 70% ethanol. The analysis of cocoa bean shell powder including proximate and color analysis. The cocoa bean shell extract analysis including antioxidant activity of Radical Scavenging Activity (RSA) DPPH, total phenolic, total flavonoid, FTIR, and total dissolved solids. The result show that North Luwu cocoa bean shell extract has a higher active compound content than Gunungkidul, and this is reflected in RSA DPPH.